Developmental and internal validation of a novel 13 loci STR multiplex method for Cannabis sativa DNA profiling. (May 2017) - Houston, Rachel; Birck, Matthew; Hughes-Stamm, Sheree; Gangitano, David
Highlights: A novel 13 loci cannabis STR multiplex method was developed and validated. Six new cannabis STR tetranucleotide markers were included. A sequenced allelic ladder was designed to genotype 101 C. sativa samples. The sensitivity is 0.13 ng DNA and the power of discrimination is 1 in 55 million. Well-balanced heterozygous peaks with minimal artifacts and stutter were observed. Abstract: Marijuana ( Cannabis sativa L.) is a plant cultivated and trafficked worldwide as a source of fiber (hemp), medicine, and intoxicant. The development of a validated method using molecular techniques such as short tandem repeats (STRs) could serve as an intelligence tool to link multiple cases by means of genetic individualization or association of cannabis samples. For this purpose, a 13 loci STR multiplex method was developed, optimized, and validated according to relevant ISFG and SWGDAM guidelines. The STR multiplex consists of 13 previously described C. sativa STR loci: ANUCS501, 9269, 4910, 5159, ANUCS305, 9043, B05, 1528, 3735, CS1, D02, C11, and H06. A sequenced allelic ladder consisting of 56 alleles was designed to accurately genotype 101 C. sativa samples from three seizures provided by a U.S. Customs and Border Protection crime lab. Using an optimal range of DNA (0.5–1.0 ng), validation studies revealed well-balanced electropherograms (inter-locus balance range: 0.500–1.296), relatively balanced heterozygous peaks (mean peak height ratio of 0.83 across all loci) with minimal artifacts and stutter ratio (mean stutter of 0.021 across all loci). This multi-locus system is relatively sensitive (0.13 ng of template DNA) with a combined power of discrimination of 1 in 55 million. The 13 STR panel was found to be species specific for C. sativa ; however, non-specific peaks were produced with Humulus lupulus . The results of this research demonstrate the robustness and applicability of this 13 loci STR system for forensic DNA profiling of marijuana samples.